IMPLEMENTASI TWO-FACTOR AUTHENTICATION PADA SISTEM INFORMASI KEUANGAN KAMPUNG BERBASIS WEB - Irvandi Reinal Ambui; Desmin Tuwohingide; Alfrianus Papuas; Miske Silangen (Smart Education, 2026)
Information security plays a crucial role in protecting the village (kampung) financial information system that manages budgeting, funding sources, planning, and reporting. Authentication mechanisms relying solely on usernames and passwords remain vulnerable to credential theft and unauthorized access. This study aims to implement Two-Factor Authentication (2FA) using Google Authenticator in a web-based Kampung Financial Information System. The system was developed using the Waterfall software development methodology. The system is integrated with a two-step verification procedure, specifically requiring that any financial data to be published to the public must first be verified by the kampung authority, namely the Head of the Kampung (Kepala Kampung). Functional testing was conducted using the Black Box Testing method to evaluate authentication and authorization features. The results indicate that the application of 2FA significantly minimizes the risk of unauthorized access and ensures data integrity before publication without reducing system usability.